Assessing day-to-day reliability of the Newtest 2000 sprint timing system - Shalfawi, S. A. I.; Tonnessen, E.; Enoksen, E.; Ingebrigtsen, J. (Serbian Journal of Sports Sciences, 2011)
The purpose of the present study was to assess the day-to-day test-retest reliability of the Newtest 2000 - sprint timing system. The reliability of the system was assessed by testing 52 Physical Education students. All participants were tested on 30 m sprint, with 10 m, 20 m and 30 m split times obtained as well. All measurements were performed on two subsequent days at the same place and time of the day with identical settings and configurations. The results from this investigation indicate that the performance variations between test day one and test day two was small and the Intra-Class Correlation (ICC) indicates a high repeatability of the students` performance during the day-to-day test-retest. In the examination of the system reliability, the results did not show any marked systematic bias (P < 0.05) in the mean difference (errors) between the measurements on the first day (test) and second day (retest) occasions. We conclude that the Newtest 2000 sprint timing system examined in this study is a reliable testing instrument for testing Physical Education students and a useful instrument for measuring running speed. However, in future studies it would be interesting to examine if the system would be able to monitor the small changes in running speed that could result from increasing the training of an already elite athlete.